Sentiment Analysis About Childfree on Gita Savitri's YouTube Content - Annisa, Fahraniar Nur; Aesthetica, Nur Maghfira (Universitas Muhammadiyah Sidoarjo, 2024)
Childfree has become a trend in modern society in the 21st century. This term refers to married couples who decide not to have children during their marriage. Although Childfree remains controversial in society due to differing opinions and perspectives on the presence of children in marriage, this research aims to explore the debate within the Childfree discourse on social media. Identification is made of how women are positioned as subjects or objects and the readers' positions in receiving the Childfree discourse in public spaces. Some perspectives, such as deontological ethics and views on human nature, do not support Childfree. However, there are also supportive views such as utilitarianism and existentialism. This research focuses on discussing Childfree from the perspectives of utilitarianism and existentialism. Secondary data used in this research were obtained from various sources such as previous research, reports, and websites. The research results show that from the perspectives of utilitarianism and existentialism, Childfree can be accepted because it considers the interests of others and is part of human rights.